2017
DOI: 10.1142/s0192415x17500914
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensis Exerts Angiogenic and Anti-apoptotic Effects Against Cerebral Ischemia–Reperfusion Injury by Activating p38MAPK/HIF-1α/VEGF-A Signaling in Rats

Abstract: This study evaluated the effects of Angelica sinensis extract [Dang Gui (DG)] administered before 60[Formula: see text]min of middle cerebral artery occlusion followed by 3[Formula: see text]d of reperfusion and investigated the involvement of mitogen-activated protein kinase (MAPK)/hypoxia-inducible factor (HIF)-1[Formula: see text] signaling in the cortical ischemic penumbra. DG was intraperitoneally administered at a dose of 0.25[Formula: see text]g/kg (DG-0.25g), 0.5[Formula: see text]g/kg (DG-0.5g), or 1[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…Stroke is accepted as the second leading cause of death in adults worldwide, which is characterized by cerebral ischemia because of disturbances for cerebral blood flow caused by thrombi or emboli. 1 - 3 Despite advances in the treatment technique, the prognosis of stroke remains poor. Till date, very limited medications such as tissue plasminogen activator are used to treat ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is accepted as the second leading cause of death in adults worldwide, which is characterized by cerebral ischemia because of disturbances for cerebral blood flow caused by thrombi or emboli. 1 - 3 Despite advances in the treatment technique, the prognosis of stroke remains poor. Till date, very limited medications such as tissue plasminogen activator are used to treat ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“… 7 - 11 Ischemia/reperfusion causes the damage of blood–brain barrier (BBB) and neurons and releases various ions, chemicals, growth factors, and neurotransmitters, which further affect the BBB permeability and aggravate the neuronal damage during cerebra ischemia. 3 , 12 , 13 Among the efforts that have been made to attenuate the I/R injury, numerous types of pretreatment measurements have been suggested by accumulating studies. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…The brain tissue sections were prepared, and subsequent immunohistochemistry (IHC) evaluations were performed as previously described [32]. Anti-ki67 antibody used in the IHC evaluation was listed in Table 1.…”
Section: Assessment Of Immunohistochemistrymentioning
confidence: 99%
“…Hurley et al [22] showed that JH also resulted in a dose-dependent increase in hippocampal BDNF and protected the brain nerves. Cheng et al [23] found that DG pretreatment protected patients from cerebral infarct and improved neurological damage by downregulating the caspase3 and upregulated p-p38 MAPK, hypoxia-inducible factor (HIF-1), vascular endothelial growth factor-A (VEGF-A). Chen et al [24] found that a Danggui Sini decoction could ebe effectively used to protect microvascular endothelial cells of islet microvasculature via PI3K/Akt/iNOS pathway.…”
Section: Discussionmentioning
confidence: 99%